Modern Capacities, Methods, and Means of Forensic Construction Investigations - A. Yu. Butyrin; E. B. Stativa (Теория и практика судебной экспертизы, 2023)
The article considers the issues of applying specific research methods in forensic construction examinations. The authors propose a classification of methods and means based on various criteria, including the impact on objects and the principles of operation. The specifics of their use in field and laboratory research have also been considered. The authors pay special attention to the use of drones for expert inspections of construction sites and associated land plots. In addition, the following methods have been presented in detail: physical and mechanical (elemental, chemical, mineralogical, phase analysis), physical (thermal analysis method), physical and chemical (instrumental methods), mechanical non-destructive methods (methods based on Fizdel, Kashkarov and Schmidt hammers), mechanical destructive methods (using test presses, bursting machines, tensile testing devices), acoustic (ultrasonic, ground-penetrating radar), electro-physical (magnetic, electric, and electromagnetic), radiation (X-ray and gamma-ray), radio wave, thermal, holographic, computer tomography, and calculation methods. It is shown that a timely replenishment of a construction-expert’s instrumental arsenal with modern methods and techniques of examination based on the latest scientific and technological advances guarantees sustainable development of forensic construction examinations as one of the most demanded areas of expert activity in Russian legal proceedings.